CdTe Based X/γ-ray Detector with MoOx Contacts - O.L. Maslyanchuk; M.M. Solovan; V.V. Brus; E.V. Maistruk; S.V. Solodin (Журнал нано- та електронної фізики)
The electrical characteristics of the Mo-MoOx/р-CdTe/MoOx-Mo heterostructures, manufactured by magnetron sputtering of molybdenum oxide thin films on CdTe semi-insulating crystals produced by Acrorad Co. Ltd were studied. Optimization of substrate conditions pretreatment and contacts deposition allowed to reduce the dark current of the detectors compared with earlier analogs and, consequently, to improve its spectrometric characteristics. The charge transport mechanisms for ensuring the low values of reverse currents in the structures were determined: the generation-recombination in the space charge region (SCR) at relatively low voltages and currents limited by the space charge at high voltages. It is shown that the heterostructure Mo-MoOx/р-CdTe/MoOx-Mo can be used for practical applications in the X- and -ray detectors.